2011
DOI: 10.1017/s0305004111000144
|View full text |Cite
|
Sign up to set email alerts
|

Numerical criteria for integral dependence

Abstract: We study multiplicity based criteria for integral dependence of modules or of standard graded algebras, known as 'Rees criteria'. Rather than using the known numerical invariants, we achieve this goal with a more direct approach by introducing a multiplicity defined as a limit superior of a sequence of normalized lengths; this multiplicity is a non-negative real number that can be irrational.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 10 publications
0
43
0
Order By: Relevance
“…The vanishing of the ε-multiplicity of an ideal is captured by the analytic spread of the ideal. Indeed, as in the case of j -multiplicity, the ε-multiplicity of I is not zero if and only if the analytic spread of I is maximal [23,41]. In particular, by Proposition 6.1 we obtain the following result.…”
Section: The ε -Multiplicity Of Edge Idealsmentioning
confidence: 72%
See 1 more Smart Citation
“…The vanishing of the ε-multiplicity of an ideal is captured by the analytic spread of the ideal. Indeed, as in the case of j -multiplicity, the ε-multiplicity of I is not zero if and only if the analytic spread of I is maximal [23,41]. In particular, by Proposition 6.1 we obtain the following result.…”
Section: The ε -Multiplicity Of Edge Idealsmentioning
confidence: 72%
“…More recently, Achilles and Manaresi introduced the concept of j -multiplicity [1], and Ulrich and Validashti proposed the notion of ε-multiplicity [41], extending the classical Hilbert-Samuel multiplicity to arbitrary ideals in a general algebraic setting. These invariants have been proven useful in commutative algebra and algebraic geometry for their connections to the theory of integral closures and Rees valuations, the study of the associated graded algebras, intersection theory, equisingularity and local volumes of divisors [11,23,24,30,41]. Recently, Jeffries and Montaño showed that these numbers measure certain volumes defined for arbitrary monomial ideals, similar to the zero-dimensional case [21].…”
Section: Introductionmentioning
confidence: 99%
“…We also prove that being weakly birational is equivalent to the equality of the above two relative multiplicities. One may be tempted to define a relative multiplicity based on the simpler function Λ(n) := λ R (Γ m (B n /A n )) instead [13]. However, this function need not be polynomial eventually [2].…”
mentioning
confidence: 99%
“…Using the multiplicity estimates of the filtrations constructed by Theorem 5, we give a different proof of the existence of ǫ-multiplicity introduced in [11]. Here ℓ(M) denotes the length of M. …”
Section: As a Corollary We Recover The Celebrated Results Of Ratliff mentioning
confidence: 99%
“…We also give an estimate on the number of times that a given prime appears in these special filtrations, and we use it to bound the length of the local cohomology modules, reproving a result of Ulrich and Validashti [11].…”
Section: Introductionmentioning
confidence: 98%